Strong Associations Between Inflammation, Pruritus and Mental Health in Dialysis Patients - Severin Schricker; Thorsten Heider; Moritz Schanz; Jürgen Dippon; Mark Dominik Alscher; Heinz Weiss; Thomas Mettang; Martin Kimmel (Medical Journals Sweden, 2019)
Pruritus, impaired mental health and inflammation contribute to morbidity in end-stage renal disease. There are no studies on all 3 conditions. We therefore obtained inflammatory parameter data (C-reactive protein and interleukin-6), pruritus data and psychological test data (36-Item Short-Form Health Survey, "Allgemeine Depressionsskala" and Toronto Alexithymia Scale-20) for 19 dialysis patients with pruritus, 20 dialysis patients without pruritus and 15 healthy controls. Non-parametric hierarchical clustering revealed 3 clusters of parameters: one mainly driven by pruritus scores (chronic kidney disease-associated pruritus cluster), one by mental health scores (mental health cluster) and one by inflammatory parameters (inflammatory cluster). Factor analysis showed strong associations (mental health cluster/chronic kidney disease-associated pruritus cluster, r=-0.49; mental health cluster/inflammatory cluster, r=-0.52; inflammatory cluster/chronic kidney disease-associated pruritus cluster, r=0.48). For the first time, complete correlations between inflammation, mental health and pruritus in dialysis patients have been established. As all 3 conditions are associated with mortality, knowledge about their interdependence helps to understand end-stage renal disease pathophysiology.